Ruthenium Carboxylate Complexes as Efficient Catalysts for the Addition of Carboxylic Acids to Propargylic Alcohols. Issue 18 (27th April 2015) - Jeschke, Janine; Gäbler, Christian; Korb, Marcus; Rüffer, Tobias; Lang, Heinrich
Abstract: Ruthenium complexes [Ru(CO)2 (PPh3 )2 (O2 CR)2 ] –3a (R = CH2 OCH3 ), 3b (R = i Pr), 3c (R = t Bu), 3d (R = 2‐ c C4 H3 O), and3e (R = Ph) – were synthesized by treatment of Ru(CO)3 (PPh3 )2 with the corresponding carboxylic acids. The molecular structures of the newly synthesized complexes in the solid state are discussed. Compounds3a –e were successfully applied as catalysts in the addition of carboxylic acids to propargylic alcohols to give the corresponding β‐oxo esters in good to excellent yields even in air. The different carboxylate ligands do not have an influence on the productivities, because the carboxylates exchange rapidly under the applied reaction conditions, as was confirmed by 31 P{ 1 H} NMR spectroscopic studies. The addition of catalytic amounts of Na2 CO3 resulted in an increase in β‐oxo ester formation. The reaction is tolerant to the use of versatile functional groups on the propargylic alcohols and carboxylic acids, revealing a broad substrate generality. In contrast to most other known catalytic systems, even sterically hindered substrates, including 2, 4, 6‐trimethylbenzoic acid, 1, 1‐diphenylprop‐2‐yn‐1‐ol, or the biologically active steroid ethisterone, were successfully converted. Abstract : Ruthenium carboxylate complexes were applied in the synthesis of diverse β‐oxo esters by the addition of carboxylic acids to propargylic alcohols. The catalytic system tolerates a broad range of functional groups and even facilitates the successful conversion of challenging substrates such as sterically demanding steroids.